Interspecific variation in fish spatial synchrony relates to reproductive traits in a highly fragmented river. (17th October 2022) - Rodrigues, Amanda Cantarute; Granzotti, Rafaela Vendrametto; dos Santos, Natália Carneiro Lacerda; Bini, Luis Mauricio; Severi, William; Gomes, Luiz Carlos
Abstract: Spatial synchrony occurs when the abundance of populations in different locations rise and fall together. This pattern is caused mainly by dispersal and spatially correlated environmental stochasticity. The levels of spatial synchrony can vary between species, yet little is known about which species traits can explain this interspecific variation. In addition, traits may have different degrees of influence on spatial synchrony levels because of their differences in plasticity. We hypothesized that conservative traits—reproductive and morphological—will best explain interspecific variation in synchrony, while those that may vary according to the environment—feeding and habitat preference—will be weakly related to this interspecific variation. We evaluated the spatial synchrony of freshwater fish species in a highly fragmented river in the Neotropical region and related the levels of synchrony to seven predictors: diet, reproductive traits (migration, fecundation, parental care and spawning), position in the water column, niche breadth, body size, body shape and average temporal occurrence of each species. The fish species showed low levels of spatial synchrony but a high interspecific variation (correlation values ranging from −0.11 to 0.41). We found that this variation was mainly related to species' reproductive traits, that is, sedentary species with partial spawning and without parental care had higher mean spatial synchrony than species with the opposite characteristics. In contrast, more plastic traits (diet and habitat preferences) were poor predictors of mean spatial synchrony. We speculate that, despite the low spatial synchrony found, if extreme impacts continue to occur in the basin at the regional scale, it may negatively affect local fish populations in a synchronous manner, resulting in increased risk of simultaneous declines. Resumo: A sincronia espacial ocorre quando a abundância de populações em diferentes locais aumenta e diminui ao mesmo tempo. Esse padrão é causado principalmente pela dispersão e pela estocasticidade ambiental espacialmente correlacionada. Os níveis de sincronia espacial podem variar entre as espécies, mas pouco se sabe sobre quais atributos das espécies podem explicar essa variação interespecífica. Além disso, esses atributos podem ter diferentes graus de influência nos níveis de sincronia espacial devido às diferenças no seu nível de plasticidade. Nós hipotetizamos que atributos conservadores – reprodutivos e morfológicos – explicam melhor a variação interespecífica na sincronia, enquanto aqueles que podem variar de acordo com o ambiente – alimentação e preferência de habitat – estão fracamente relacionados a essa variação interespecífica. Nós avaliamos a sincronia espacial de espécies de peixes de água doce em um rio altamente fragmentado na região Neotropical e relacionamos os níveis de sincronia com sete preditores: dieta, características reprodutivas (migração, fecundação, cuidado parental e desova), posição na coluna d'água, amplitude de nicho, tamanho do corpo, forma do corpo e ocorrência temporal média de cada espécie. As espécies de peixes apresentaram baixos níveis de sincronia espacial, mas uma alta variação interespecífica (valores de correlação variando de −0, 11 a 0, 41). Essa variação esteve relacionada principalmente às características reprodutivas das espécies, ou seja, espécies sedentárias com desova parcial e sem cuidado parental apresentaram maior sincronia espacial média do que espécies com características opostas. Em contraste, características mais plásticas (dieta e preferências de habitat) foram preditores ruins da sincronia espacial média. Também especulamos que, apesar da baixa sincronia espacial encontrada, se impactos extremos continuarem a ocorrer na bacia em escala regional, eles podem afetar negativamente as populações locais de peixes de forma síncrona, resultando em aumento do risco de declínios simultâneos.